Topos, ethos and aesthesis of national-state myth in modern culture - O. P. Polishchuk (Ukrainian Cultural Studies, 2018)
The article touches upon the issue of the need to study the phenomenon of “national-state myth” more intensively in the modern conditions of life of the society. The analysis of the national-state myth specifics is carried out not only as a kind of political myth, but firstly as a socio-cultural phenomenon. We assert that among the newest myths, which significantly affect the value orientations and life standards of each society, a special place is occupied exactly by the national-state myth. Such myth is called to form public opinion about the state as representative and defender of key nation’s interests and also culture differences. Such myth becomes especially popular in the crisis conditions of social processes in the state and its relationships with other countries. This myth is created in interests of those social strata, which occupied main positions in the management of the state. It is not necessary for such social strata to be the representatives of main nation in this society and its culture. A basic source of its promotion in society is an influence of mass communications on public consciousness in the process of symbolic production. Ethos of the “national-state myth” phenomenon in modern society is aimed at the formation of pride for nation and its culture, patriotism in the broad strata of society through an addressing to the historical events, special achievements of nation and so on. But interest to such myth and its popularity provide aesthetically beautiful moments during distribution of such social product in a symbolic exchange in modern society and its national culture. The research of the origins and functional features of "national-state myth" is realized, and they are compared to the origins and functional features of the classic, archaic myth. The specificity of these constructs of the ideal spiritual life in modern conditions is investigated, and the role of ethos and aesthesis of the “state’s art mythos” phenomenon is researched too. Also the article analyzes the formal and aesthetic aspects of the content of the information in such myth. To our opinion a modern national-state myth actually is an artistic myth on a form its presentation in facilities of mass communication. He uses facilities and possibilities of human artistic thought. Therefore modern cultural space which tested total influence of such myths appeared as a “place for a game senses and offenses” in the removal of contemporary from reality. We assert that it is liked to be a man not through insufficiency of knowledge, but because many modern people miss. Modern Europeans miss often, but yet presently they are often afraid of changes in their life through a crisis in society. Therefore such myth not only strengthens patriotism of citizens of country. Such myth creates the illusion of stability for them, gives them a confidence in itself and to the state. A modern man presently often has a desire to go from reality from its much by numeral problems in the idealizing world. Such myths give the alarmed people to calm down and enjoy life as spectacle in a theater or a circus. Myth of the “messiah calling of country” is analyzed as an example of state myth. Such myth once created terms, as ideological basis, for the representatives of one nation, to create a strong state. But in modern terms neglect to the people of other nations is drawn. It is therefore needed to mark that such myth becomes in modern terms a basis for the conflicts between different peoples. The question concerns propaganda of national exceptional nature from the side of any totalitarian states. Therefore such a myth creates terms for enmity between different nations and peoples, develops in man contempt to other people. We assert that national character of any modern nation appears in various aspects. E.g., attitude to the past, role of the country in civilization history, national historical myths, address to folk beliefs, ceremonies, and mysticism. Ethos of national-state myth not only speaks to the elements of national character of specific group of people, also causing changes in it. They are not always positive; vice versa such changes through growth of role of state myth for  spiritual life of nation are a certificate of deep crisis in this society. The overstatement of the value for history of humanity conduces to inadequate and illusive perception of present life conditions of society. A man as a result of infatuation for such a myth becomes inadequate to estimate itself and other people.For his logic, acts or thoughts change. In fact, this is an a-logic. It is possible to say that under the action of such myth a man loses correct social standards of conduct. It is simply played, and a game is perceives as a real life.
Keywords: Myth, ‘National-state Myth’, Ethos of Myth, Aesthesis of Myth, Symbol, Symbolic Production, Symbolic Exchange, Mass communications, Popular Culture